IMPACT OF UTERINE MYOMA ON OBSTETRIC AND PERINATAL OUTCOMES - G.S.KARIMOVA (Scholar Express Journals, 2022)
The combination of uterine myoma and pregnancy ranges from 0.5% to 6%. The course of pregnancy with uterine myoma, in addition to the growth of nodes and impaired nutrition in them, includes: threat of termination in different gestational periods, development of preeclampsia, fetoplacental insufficiency, delayed fetal development syndrome, placenta detachment, placenta previa, abnormal fetal position. Pregnant women with uterine myoma were found to have one or more extragenital abnormalities, which significantly reduced the immunological status of the pregnant woman and the rate of gestational and perinatal complications.
Keywords: Uterine Fibroids; Gestation; Placenta; Fetus